PENGARUH TEKNIK BERMAIN PERAN UNTUK MENINGKATKAN SELF ESTEEM PADA SISWA DI SMPN 4 PEKANBARU MELALUI BIMBINGAN KELOMPOK - Herniza, Dian Nur; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to examine the effect of role playing techniques to improve student self-esteem in SMP N 4 Pekanbaru. This type of research is quantitative research with experimental methods using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the scale of student self-esteem measurement which consisted of 50 items before validation, and after validation the number of valid items was 35 items with a validity of 0.594 and a reliability of 0.953. The subjects of this study were 7 students who were identified as having low self-esteem. The data analysis technique used was non-parametric statistical techniques using the Rank Spearman test. The results of the study prove the accepted research hypothesis. Therefore, from the results of the Rank Spearman test, r = 0.821 while the correlation coefficient r2 is 0.674. Thus there is the influence of role playing techniques on student self-esteem by 67% in SMP N 4 Pekanbaru. From the Wilcoxon test results obtained (Asymp.Sig) 0.018 <0.05, it can be concluded that there are differences in students' self-esteem values before and after the treatment of role playing techniques was given.Keywords:role playing, self esteem